Bonding strength of stainless steel rebars in concretes exposed to marine environments. (30th May 2018) - Calderon-Uriszar-Aldaca, I.; Briz, E.; Larrinaga, P.; Garcia, H.
Highlights: Rebar-concrete adherence studied in simulated marine environments. Influence of stainless steel rebars: 304, 316, 2001, 2205, 2304. Influence of rebar diameter: 12 and 25 mm. Effects of cement content and w/c ratio related to alkalinity and porosity. Adherence loss due to of corrosion over time. Abstract: Many studies have corroborated the use of Stainless Steel Reinforcements (SSR) for structures in corrosive environments. However, even though the conditions for their employment are specified in different standards, their use is always tied to the same requirements for standard carbon steel rebars (B500SD), among which an equivalent carbon content for weldability that is inappropriate for SSR. Further studies are therefore needed to develop suitable standards that will focus on addressing not only the content, but also the technical advantages of SSR for structural engineering under specific conditions. The results of this study show improvements in the maximum bond strength behaviour of different SSRs in simulated marine environments, in comparison with B500SD, in terms of several variables: Bond index, curing time, w/c ratio, and corrosion. Specifically, the test results showed that: (a) the Bond index was not a suitable parameter for the evaluation of the bonding strength of SSR; (b) the curing time increased the bonding strength of Lean Duplex Stainless Steel (LDSS); (c) a higher w/c ratio tended to decrease bond strength, although less so in LDSS; and, (d) corrosion reduced bond strength, especially in B500SD.